Participation in clinical trials improves outcomes in women's health: a systematic review and meta‐analysis. (14th February 2017) - Nijjar, SK; D'Amico, MI; Wimalaweera, NA; Cooper, NAM; Zamora, J; Khan, KS
Abstract : Background: Previous reviews examining the effect of participation in trials on outcomes have not consistently shown benefit. Obstetrics and gynaecology is a unique disease area posing challenges for both researchers and patients. Objectives: To determine whether participation in randomised controlled trials (RCTs), compared with non‐participation, has a beneficial effect on women's health. Search strategy: Medline, Embase, the Cochrane Library, and PsycInfo were searched up to December 2015. Selection criteria: We selected studies that reported the same clinical outcomes for participants in a women's health RCT and a comparable non‐participant cohort. Data collection and analysis: Data were extracted on quality, characteristics and study results. Outcomes were compared using logistic regression. Main results: There were 21 relevant studies (20 160 women, 4759 outcome events). Trial participants, compared with non‐participants, had 25% better odds of improved outcomes on average (OR 0.75; 95% CI 0.64–0.87; I 2  = 64.3%). The beneficial effect of participating in a trial was larger in comparisons where: RCTs were of high quality (OR 0.62; 95% CI 0.50–0.76) versus low (OR 0.92; 95% CI 0.74–1.16); and RCT intervention was not available to non‐participants (OR 0.57; 95% CI 0.47–0.69) versus when it was (OR 1.13; 95% CI 0.89–1.44). The effect of trial participation was not influenced by effect size within the RCT ( P  =   0.48), whether funding was received or not ( P  =   0.13), whether non‐participants received any treatment or not ( P  =   0.49), and the quality of the comparison of RCT participants with non‐participants ( P  =   0.88). Conclusions: Women participating in RCTs on average experienced better outcomes compared with those outside trials. Tweetable abstract: Participants in obstetric and gynaecology RCTs experience better outcomes compared with non‐participants. Tweetable abstract: Participants in obstetric and gynaecology RCTs experience better outcomes compared with non‐participants. This article includes Author Insights, a video abstract available athttps://vimeo.com/rcog/authorinsights14528 .